CYBERSECURITY CHALLENGES AND OPPORTUNITIES IN THE INTERNET OF THINGS (IOT): COMBINING ARTIFICIAL INTELLIGENCE, IOT AND CYBERSECURITY - Ulichev, Oleksandr; Yarovy, Roman; Zadorozhny, Kostyantyn (Ukrainian Information Security Research Journal, 2024)
The aim of the paper is to explore the challenges and opportunities related to cyber security in the context of the Internet of Things (IoT) and the combination of artificial intelligence (AI) with IoT, known as AIoT. The work examines the evolution of IoT to AIoT, the importance of cybersecurity in AIoT, and the various challenges that arise from the increasing number of networked devices and the growth of data. The study also examines cybersecurity strategies for AIoT, including network communication protection, the use of artificial intelligence in cyber attack detection and prevention systems, access control and identification, and operational monitoring and anomaly detection. The article examines the issue of standardization and regulation in the field of AIoT cybersecurity and future directions of development in this field, in particular, attention is paid to the following areas: the use of blockchain technologies, the expansion of the role of artificial intelligence in AIoT cybersecurity. The final part of the article contains the conclusions of the study, recommendations for further research and improvement of cyber security in AIoT.